Video Profil SMK Animasi Bina Nusantara Batam Berbasis Motion Graphic - Budi Prio Utomo (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2020)
Bina Nusantara Animation Vocational School Batam is an educational institution founded in 2018 that needs utilization of technological developments on the medium promotion, both on print and online medium. However, In the previous year, there were only print medium such as billboard, banner, brochure and others so that many people do not know about the school profile in detail causing them to directly visit the school. Creating Motion graphics on the video profile of Bina Nusantara Animation Vocational School Batam applied multimedia design method of Villamil-Molina consisting of development, preproduction, production, postproduction, and delivery, then this video profile was conducted by employing alfa and beta testing as well as the product feasibility analysis to determine that it is appropriate to be published to the public via various media. The product testing result shows that this video profile meets the eligibility indicators which are from 100% of display element aspect, 99% of knowledge aspect and 100% of comprehension aspect. In conclusion, the respondents agreed that the product is suitable for publication..